Rancang Bangun Sistem Inventaris Fasilitas Kantor Dinas Tenaga Kerja Dan Transmigrasi Provinsi Riau: Inventory Information System Facilities Office Of Manpower And Transmigration Of Riau Province - gusti, Agusti Anisa (Indonesian Journal of Informatic Research and Software Engineering (IJIRSE), 2021)
Inventory is a registration record of office-owned items used in carrying out tasks. Inventory is an activity to carry out themanagement, administration, regulation, recording and registration of inventory items or property rights. The problems in inventory management that occur in this agency are that it takes a long time to find data on the facilities of the desireditem, the resulting report is unsatisfactory, and errors often occur in data input. Therefore, to solve some of the problemsthat occur, an office facility inventory management information system is needed, which can make it easier to input data,easy to search for data and also produce good and accurate reports. The analysis and design stages of this system use the Object Oriented Analysis Design (OOAD) technique, the system development method uses the waterfall method and the system design uses the Unified Modeling Language (UML) diagram. The final result of this practical work is in the form of an information system that can provide facilities for agencies in the process of managing inventory data so that it makes it easier for agencies to manage inventory data for the offices of the Riau Province Manpower and Transmigration Office.